Faktor yang Memengaruhi Kemiskinan di Provinsi Jawa Timur Tahun 2014 - Salihati Hanifa; Arief Wibowo (Universitas Airlangga, 2017)
Indonesia is one of the developing countries that still experience classic problems such as poverty. Poverty is a classic multidimensional problem, because it is caused by various factors such as Open Unemployment Rate (OUR), percentage of contraception’s user and Human Development Index (HDI). This study aims to analyze determine the effect of Open Unemployment Rate (OUR), percentage of contraception’s user and Human Development Index (HDI) on the percentage of poor people in East Java. This study uses unobtrusive method and uses secondary data in the form of publication data of Badan Pusat Statistik (BPS) of East Java Province. The unit of analysis in this study is 38 districts/cities in East Java. The dependent variable in this study is the percentage of poor people in East Java Province, while the independent variables are Open Unemployment Rate (OUR), percentage of contraception’s user and Human Development Index (HDI). The result based on multiple linear regression analysis shows that the factors can influence the percentage of poor people are percentage of contraception’s user (p = 0.015) and HDI (p = 0.000). The government is expected to evaluate the programs that have been implemented and related to poverty alleviation.